1992
DOI: 10.1002/sia.740190196
|View full text |Cite
|
Sign up to set email alerts
|

Changes induced in the surface characteristics and catalytic activity of amorphous Cu‐Zr by hydrogen pretreatment

Abstract: Hydrogen-treated amorphous Cu,,Zr,, alloy ribbon exhibits the development of characteristic formations (hemispheres) in a circular arrangement (as revealed by SEM) on both sides of the ribbon, in parallel with copper enrichment (determined by AES) and partial crystallization (determined by differential scanning calorimetry). The extrusion of pure copper is considered to be caused by hydrogen diffusing into the bulk through existing surface defects. As a consequence of the surface and structural changes, steady… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Similarly, decomposition of Zr-Cu alloys under hydrogen was reported to proceed by phase separation leading to the formation of ZrH 2 , Cu and Cu-Zr phases [33], [45], [47]. Such a structural transformation under hydrogen induced fast Cu segregation to the surface [47]. An additional increase in temperature to 500 °C in Fig.…”
Section: Thermal Stability Under Hydrogenmentioning
confidence: 81%
See 1 more Smart Citation
“…Similarly, decomposition of Zr-Cu alloys under hydrogen was reported to proceed by phase separation leading to the formation of ZrH 2 , Cu and Cu-Zr phases [33], [45], [47]. Such a structural transformation under hydrogen induced fast Cu segregation to the surface [47]. An additional increase in temperature to 500 °C in Fig.…”
Section: Thermal Stability Under Hydrogenmentioning
confidence: 81%
“…5b) cannot be related to the alloy crystallisation, rather possible structural relaxation or some reordering of the amorphous structure [33]. Similarly, decomposition of Zr-Cu alloys under hydrogen was reported to proceed by phase separation leading to the formation of ZrH 2 , Cu and Cu-Zr phases [33], [45], [47]. Such a structural transformation under hydrogen induced fast Cu segregation to the surface [47].…”
Section: Thermal Stability Under Hydrogenmentioning
confidence: 99%
“…HF-Treated Alloy. Etching in HF solution is a successful method to activate Zr-containing alloys because HF acts as a selective reagent to dissolve zirconium species from the surface. HF dissolution (treatment with 0.035 M HF for 1 h at 298 K) resulted in a weight loss of 36%. Since dissolution of Pd in HF is much slower than that of Zr/ZrO x , a composition of Pd 40 Zr 60 for the etched sample can be calculated.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the effect of gaseous hydrogen at atmospheric pressure on the catalytic activity is found to be moderate even after prolonged application at elevated temperature [5,16,17]. Studies using such hydrogenative pretreatment have indicated significant changes in both the bulk and the surface structure [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Studies using such hydrogenative pretreatment have indicated significant changes in both the bulk and the surface structure [17][18][19][20]. However, the effect of high-pressure hydrogenation of zirconium-containing amorphous ribbons on their catalytic performance has not been investigated.…”
Section: Introductionmentioning
confidence: 99%